2021
DOI: 10.1177/20552076211047390
|View full text |Cite
|
Sign up to set email alerts
|

Use and performance of machine learning models for type 2 diabetes prediction in clinical and community care settings: Protocol for a systematic review and meta-analysis of predictive modeling studies

Abstract: Objective Machine learning involves the use of algorithms without explicit instructions. Of late, machine learning models have been widely applied for the prediction of type 2 diabetes. However, no evidence synthesis of the performance of these prediction models of type 2 diabetes is available. We aim to identify machine learning prediction models for type 2 diabetes in clinical and community care settings and determine their predictive performance. Methods The systematic review of English language machine lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Most studies tend to use machine learning algorithms such as decision trees, random forests, SVM, logistic regression, and neural networks to build T2DM prediction models, with AUC values ranging from 0.7 to 0.9 33 , 34 . Wang J et al adopted three commonly used machine learning algorithms (RF, SVM, and BP-ANN) combined with the elastic network (EN) to simulate and predict blood glucose status in China.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies tend to use machine learning algorithms such as decision trees, random forests, SVM, logistic regression, and neural networks to build T2DM prediction models, with AUC values ranging from 0.7 to 0.9 33 , 34 . Wang J et al adopted three commonly used machine learning algorithms (RF, SVM, and BP-ANN) combined with the elastic network (EN) to simulate and predict blood glucose status in China.…”
Section: Discussionmentioning
confidence: 99%
“…The main implications of ML models concern various fields of medicine: that is, prediction in clinical and community care settings of chronic diseases, decision-making behaviours, clinical decision support and enhancement of efficiency of medical imaging. 10 In particular, electronic health records and electronic support systems based on algorithms could enhance the compliance with standards, avoid preventable errors and tailor the treatment on the basis of the specific characteristics and needs of the patients. 11 12 The aim of the study is to investigate the impact of AI algorithms on drug management in primary care settings.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…They found supervised learning methods dominating the diabetes research efforts (reported in 85% of the studies considered) than unsupervised learning (15%) with SVM as the most popular classifier used. De Silva et al ( 2021 ) proposed a protocol for carrying out systematic review and meta-analyses of ML predictive modeling studies for T2D on the basis of their use and performance effectiveness at clinical as well as community levels. The authors state that most of the existing systematic reviews in the area of T2D have considered traditional modeling studies only, with very less attention given to ML studies.…”
Section: Introductionmentioning
confidence: 99%